The Exponential Rise of Teledentistry and Patient-Oriented Protective Measures in Southeast Asian Dental Clinics: Concerns, Benefits, and Challenges - Anand Marya; Adith Venugopal; Mohmed Isaqali Karobari; Pietro Messina; Giuseppe Alessandro Scardina; Aravind Kumar Subramanian (International Journal of Dentistry)
In the Southeast Asian region, various policies have been advocated by health regulatory bodies that entail protective measures such as face masks, gloves, maintaining distance in public areas, and more. These protective measures are aimed at helping reverse the growth rate of the coronavirus. Dentists in this region have incorporated several changes to their practices to help minimize risks of person-to-person transmission inside dental offices. This narrative review aimed to provide an in-depth overview of the current situation in the Southeast Asian region regarding the use of teledentistry during the pandemic. Teledentistry involves the transfer of patient information across remote distances for online consultation and treatment planning. A few years back, it used to be a lesser-known entity but has seen an exponential rise in its incorporation into dental practices all around the Association of Southeast Nations (ASEAN) region. Many clinics in the Southeast Asian region have started using online consultations to ensure that patients can be diagnosed or followed up during their treatment. Teledentistry is the clear answer in the coming months as it will help reduce the risk of virus transmission and help patients get access to oral healthcare and dentists to see their patients. This article reviews the current pandemic situation in the ASEAN region, the recent evidence, and the scope of teledentistry. It also provides recommendations for the future and sheds light on the different types of teledentistry and how it can be incorporated into practices by regulatory authorities in this region.